(3Odjdc deWHN Befs - (3JGL GdOjf, ejs; (3UdGM, eQhIs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2025)
(3cJGH Odjdc deWHN Bef O(B. (3ej JGL GdOjf (B. (3aj YGde edjA HGdJMOjGJ GdZPGFjI, CUHM ef GdVQhQj Cf fYQa cja fMej CfaSfG hCSQfG ef GdeNGWQ GdNajI aj GdWYGe(B. (3cJGH zOdjdc dZPGA Bef y djS eLQO Odjd fXQj, Hd gh eQLY Yedj jVY Hjf jOjc NWhGJ HSjWI heDKQI dVeGf JbOje WYGe UMj hBef cd jhe(B. (3eMJhi Yedj hhGbYj eHfj Ydi NHQI SfhGJ aj eLGd SdGeI GdZPGA, hYed eHGTQ eY eDSSGJ YGdejI eKd GdajaG hhRGQI GdML hGdYeQIs
Keywords: (3GdGbJUGO GdefRdjs